The Contradiction of Imposing BPHTB on the Creation of Unpayment of PPJB with the Principle of Convenience - Megah Hanny Tarigan; Gratianus Prikasetya Putra; Arsin Lukman (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This paper aims to analyze the imposition of tax on the acquisition of land and building rights (Bea Perolehan Hak atas Tanah dan Bangunan – BPHTB) after the signing of a Preliminary Sale and Purchase Agreement (Perjanjian Pengikatan Jual Beli – PPJB), particularly Unpayment of PPJB, based on the principle of convenience. This paper uses the doctrinal legal research method to study the imposition of BPHTB on Unpayment of PPJB based on the principle of convenience. The study employs secondary data in the form of primary and secondary legal materials to address the research questions. This study concludes that imposing BPHTB after signing Unpayment of PPJB goes against the principle of convenience introduced by Adam Smith and used as a tax concept worldwide. Imposing BPHTB at the time of Unpayment of PPJB clearly contradicts this principle because BPHTB is collected at an inappropriate time: when there has been no transfer of land rights from the seller to the buyer. This study is expected to contribute to the development of legal science, particularly in the domain of tax law. It is also hoped that this research will serve as a basis for policymakers to formulate regulations related to the collection of BPHTB on Unpayment of PPJB, in accordance with the principle of convenience. This study provides an analysis of the imposition of BPHTB on Unpayment of PPJB, based on the principle of convenience. A review of the extant literature reveals an absence of studies that specifically address this issue. This constitutes the novel aspect of this study.